Qualifying ultrathin alumina film prepared by plasma-enhance atomic layer deposition under low temperature operation - Bootkul D. (2017)
© 2017 Elsevier B.V. Preparation of ultrathin alumina (Al 2 O 3 ) films through Plasma-Enhanced Atomic Layer Deposition (PE-ALD) at low substrate temperature is discussed. The present work aims to investigate the physical mechanism of the PE-ALD deposition process and also the characteristics of the ultrathin alumina films on silicon 〈100〉 wafer deposited using the technique. The deposition was performed using trimethyl aluminum (Al (CH 3 ) 3 ) as the precursor and argon gas for purging. During deposition, the target temperature was kept constant at ~ 80, 100 and 150 °C and the pressure was ~ 1.3 × 10 − 2 Pa. Two deposition cycles were tested, 400 and 800 cycles. As for understanding the process, the films deposited with and without oxygen plasma were compared. Various thin film characterization techniques, including Atomic Force Microscope (AFM), ellipsometry, Raman spectrometry measurement, X-ray diffraction (XRD), and indentation technique, were applied for investigating the film properties. A transmission electron microscope (TEM) equipped with high-angle annular dark-field imaging line scan modes and energy-dispersive X-ray spectroscopy acquisition was used for imaging thin film cross-sections. We found that the number of deposition cycles did not affect the substrate surface roughness as evidenced by AFM images. The mechanical property, the hardness of the film deposited with 800 cycles and plasma was the best. Raman spectroscopy measurements showed that a Al-O-Si phase exists when the films were deposited at 100 °C and 150 °C for 400 and 800 cycles under oxygen plasma atmosphere. While no Al-O-Si phase existed after the same number of ALD deposition cycle without plasma. Results from XRD measurements indicated that the films deposited at 100 °C and 150 °C for 400 and 800 cycles under oxygen plasma atmosphere has an Al-O structure. TEM images clearly displayed the interface between the thin films, SiO 2 interface layers and Si substrates. As for the sample deposited at 80 °C, an Al 2 O 3 film was hardly seen, but when increasing the deposition temperature to 100 °C and 150°, films started to build on top of the substrate. However, for all deposition conditions, TEM revealed that the amounts of carbon atoms in the reaction site remained relatively high.